Coexistence of resistance switching and negative differential resistance in the α-Fe2O3 nanorod film. Issue 26 (15th June 2016) - Cai, Yunyu; Yuan, Qinglin; Ye, Yixing; Liu, Jun; Liang, Changhao
Abstract : The coexistence of resistance switching behaviour and the negative differential resistance phenomenon was presented in the α-Fe2 O3 nanorod film that was in situ grown on a fluorine-doped tin oxide glass substrate. The migration of inner defects is revealed to be closely related to the switching behaviours. Abstract : We report the coexistence of resistance switching (RS) behavior and the negative differential resistance (NDR) phenomenon in the α-Fe2 O3 nanorod film grown in situ on a fluorine-doped tin oxide glass substrate. The reversible switching of the low- and high-resistance states (LRS and HRS, respectively) of the film device can be excited simply by applying bias voltage. The switching from the HRS to the LRS was initiated in the negative bias region, whereas the NDR process followed by the reversion of the HRS occurred in the positive bias region. With the increase in compliant current (CC), the carrier conduction models of the LRS and the HRS both changed and the current–voltage ( I – V ) relationships in the NDR region were seriously affected by the thermal process according to the level of applied CC. The co-existence of RS and NDR was possibly caused by defects during migration, such as oxygen vacancies and interstitial iron ions, which were formed in the α-Fe2 O3 nanorod film. This work provided information on the ongoing effort toward developing novel electrical features of advanced transition metal oxide devices.